Solar energy : the state of the art : ises position papers. - International Solar Energy Society ISES; Gordon, Jeffrey, ....- (London : James and James, 2001)
Solar and natural resources for a better efficiency in the built environment Glazings and coatings Selectively solar-absorbing coatings Solar collectors Solar water heating Photovoltaic physics and devices Solar concentrators The cost of pollution and the benefit of solar energy Solar process heat: distillation, drying, agricultural and industrial uses Solar resource assessment: a review Solar thermal electricity Wind energy review
Keywords: Photovoltaic (pv).; Windenergie; Zonne-energie.